Alleviating Active Labor Pain: The Impact of Virgin Coconut Oil (VCO) Back Massage During the First Stage of Labor - Utami, Iis Tri; Putri, Novi Anggista; Besmaya, Beniqna Maharani; Puspita, Pipit Yulia (PT FORMOSA CENDEKIA GLOBAL, 2024)
Labor pain is one of the most intense sensations experienced by women during childbirth, particularly during the first stage of labor. This study aimed to evaluate the effect of back massage with Virgin Coconut Oil (VCO) on the intensity of active labor pain during the first stage. The research employed a quantitative, pre-experimental one-group pretest-posttest design, involving 18 mothers in active phase labor at IMP Restu Bunda, West Tulang Bawang Regency. Pain levels were measured using the Visual Analog Scale (VAS) before and after the back massage with VCO. Results showed that the average labor pain intensity before the intervention was 7.0, and after the back massage with VCO, the average pain decreased to 5.2. Statistical analysis using the Wilcoxon test revealed a significant reduction in pain intensity (p-value = 0.000), indicating that back massage with VCO effectively reduced labor pain. Seventeen respondents reported a decrease in pain, while only one respondent experienced no change. The findings suggest that back massage with VCO is a viable non-pharmacological method for managing labor pain, with minimal side effects.